Conceptualising Luxury Brand Attachment - Shimul, Md Anwar Sadat (Curtin University, 2018)
This research conceptualises luxury brand attachment and develops a measurement scale for the construct. Underpinned with self-expansion and social identity theory, a research model is proposed with a set of hypotheses to investigate the inter-construct relationships. The self-congruity aspect within the luxury brand attachment construct is postulated to be moderated by the influence of consumers’ public self-consciousness and the product’s private/public status. The findings of this research will provide meaningful insights for academics and practitioners.